Needs Analysis for Security Guards English Program - Raphita Lestari Manulang; Susilowaty Susilowaty (Lembaga Riset dan Pengabdian Masyarakat Institut Bisnis Nusantara, 2022)
Mastery of English has become one of the significant requirements for interacting with other individuals, especially in the work environment. This has become a necessity for almost all employees who work in various sectors to use English as a means of communication. The expectation to use English has also been noticed by security officers, especially those who work in busy business areas. This study focused on needs analysis to identify the demand for security guards for English. The Design and Development Research approach was used in this investigation. A survey was conducted to determine the security guards' linguistic requirements. Following that, the statistical data were examined and used to create a syllabus that centered on resources and activities for the students. A semi-structured interview was also done to provide adequate understanding and comments on the materials and activities chosen. The importance of English in the workplace has been discovered. The most important skills they employ to support their profession as security guards are listening and speaking. Roleplaying and text-based language instructions are recommended as stimulating and meaningful strategies for learners to acquire the target language.